Challenges in the design of crop revenue insurance. Issue 1 (5th May 2015) - Professor Lysa Porth and Professor ßKen Seng Tan, Assistant; Goodwin, Barry K.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The federal crop insurance program has become the cornerstone of US agricultural policy. Since its introduction in the mid-1990s, crop revenue insurance has grown in prominence and now represents nearly 90 percent of liability for major crops. The pricing and design of revenue insurance raises a number of important challenges. The 2014 Farm Bill brought about several important changes in the program, resulting in a moving target for analysts and researchers. The paper aims to discuss these issues. Design/methodology/approach – The risks are of a multivariate nature and are likely to be highly dependent on one another. The crop insurance setting is also constantly changing, with technological changes in production practices and highly volatile commodity prices. Compounding these challenges is the fact that US policymakers continually change the program. Findings – The program has indeed undergone many changes and a number of important research questions need to be addressed. Originality/value – Original research based upon recent policy.